Ratcatcher - Portman, Rachel 1960- (<<The>> Criterion Coll., 2002)
A haunting evocation of a troubled Glasgow childhood. Set during Scotland's national garbage strike of the mid-1970's, Ratcatcher explores the experiences of a poor adolescent boy as he struggles to reconcile his dreams and his guilt with the abjection that surrounds him.
1.85:1 aspect ratio - new digital transfer, enhanced for 16x9 televisions and approved by Lynne Ramsay
Orig.: Großbritannien, Frankreich 1999
Keywords: Kind; Children -- Drama; Feature films -- Great Britain; Foreign films; Großbritannien; Glasgow (Scotland) -- Drama